Respuesta :
Answer:
[tex]f(-\frac{1}{2}) = 1[/tex]
[tex]g(-\frac{1}{2} ) = -\frac{3}{2}[/tex]
Step-by-step explanation:
Given the function [tex]f(x) = 4x + 3[/tex] and the function [tex]g(x) = 3x[/tex], to evaluate for [tex]x=-\frac{1}{2}[/tex], you need to substitute it into each function.
Then, for the function f(x), when [tex]x=-\frac{1}{2}[/tex], you get:
[tex]f(-\frac{1}{2}) = 4(-\frac{1}{2}) + 3[/tex]
[tex]f(-\frac{1}{2}) = 4(-\frac{1}{2}) + 3[/tex]
[tex]f(-\frac{1}{2}) = -\frac{4}{2}+ 3[/tex]
[tex]f(-\frac{1}{2}) = -2 + 3[/tex]
[tex]f(-\frac{1}{2}) = 1[/tex]
For the function g(x), when [tex]x=-\frac{1}{2}[/tex], you get:
[tex]g(-\frac{1}{2} ) = 3(-\frac{1}{2})[/tex]
[tex]g(-\frac{1}{2} ) = -\frac{3}{2}[/tex]
Answer:
f(-1/2) = 1
g(-1/2) =-3/2
Step-by-step explanation:
f(x) = 4x+3
Let x = -1/2
f(-1/2) = 4(-1/2) +3
f(-1/2) = -2 +3
f(-1/2) =1
g(-1/2) = 3(-1/2)
= -3/2